Trade Union Advisory Medical Officers - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
1920 1920 1920s 9 pages funds to special areas according either to population or number of Trade Unionists. Had this been done over a series of years, say in a large city like London, the Trade Unionists of London, instead of having their yearly contributions scattered over the voluntary Hospitals in various districts, on whose policy or administration of method of appointment of officers they have absolutely no control or voice would have been able to have a voluntary Hospital of their own, subject to their policy, influence and control, manned by their specialists and sympathisers combined with an efficient ambulance system for bringing their Trade Union members from any district. Arrangements could then easily be megotiated [negotiated] with other Voluntary Hospitals for treatment in special cases and under special circumstances, and with this lover of a general hospital of their own, Trade Unionists will be in a much more favoured position as far as hospital medical treatment is concerned than they are at present. Anyone with even a limited experience of Hospital life knows that occasionally things are done which ought not to be done. The young surgeon is paid in the growing experience accruing to him for his position on the Hospital Staff, and in exchange for this he forgoes the monetary consideration. The surgeons exist for the patients, not the patients for the surgeons. In many of the smaller hospitals round London to-day the surgeon pays a hurried visit weekly or bi-weekly, performs the operations got ready for him for the resident, and leaves the rest of the work to the resident. All or most of the voluntary Hospitals in the country are suffering from a financial crisis, as the result of a faulty financial policy, and Trade Unionists merged in the general community will suffer with the rest of the patients in the present and increasing shortage of hospital beds. Had a Trade Union Hospital existed it would have been a tower of strength at present. Some Trade Unions have at present their Convalescent Homes supervised by doctors who have no interest and indeed are violently opposed to the Labour movement, and no thought of amalgamating these under a Labour medical staff has received consideration up to the present. (B) General Medical Treatment of the General Population. Many complaints are being made against the present panel system for insured patients. On the whole, however, the available evidence is that it is an improvement on the old ''club practice" system. In a previous memorandum, it has been suggested how members of Trade Unions in a special or in particular districts should combine together voluntarily as far as possible, at the request of their Union branch, and go on to the panel of one particular medico who should be chosen because of sympathy in a general way with Labour ideals. The very thought that when anything goes wrong, the whole of the members of the Union or this panel may move en bloc to another practitioner would provide some stimulus to more than ordinary attention of the panel patients. But this phase of the question involves the whole question of the relationship of Medicine to the community, and as such is outside the scope of thir memorandum. (F) Labour Colleges. There are two well-known Labour educational Colleges in existence, viz: Ruskin College, Oxford, and the Labour College, Earl's Court, London. There are rumours of the probability of a Co-operative Labour college. As part of the Labour organisation, it it suggested that lecturers on Public Health from the Labour point of view should be appointed to these colleges, so that the workers may be kept in touch with the modern ideas of public health, and the advancement of medical treatment and science and research, and to meet, counter and rebutt the pronouncements and scares of the usual conventional medical conferences. The 36/H24/11